Konsep Pendidikan Insan Kamil Dalam Perspektif QS. An-Nahl Ayat 78 - Tulus Muthofa; Aisyah Amalia Putri (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2022)
The purpose of this research is to explain how the concept of insan kamil education from the perspective of QS. An-Nahl verse 78. This research uses a qualitative approach. The research method used is library research. The data sources used are divided into two, namely primary and secondary. The primary data source is QS. An-Nahl verse 78. While secondary data is obtained from data from several scientific journals, papers, results of previous research, and books that talk about similar themes. The results of this study are the meaning of the concept of insan kamil education based on QS. An-Nahl verse 78, describes that human potential is in the form of hearing, sight, and heart to be used as well as possible. The purpose of the concept of insan kamil education is a perfect human being, which has the following main characteristics: first, having a healthy, strong, and skilled body; second, intelligent and clever; and third, having a high-quality spiritual. The application of the concept of human education based on QS. An-Nahl verse 78 can be adapted to the concept of Bloom's taxonomy theory. Keywords : Education, Kamil People.